Platelet‐neutrophil complex formation—a detailed in vitro analysis of murine and human blood samples. Issue 5 (17th November 2015) - Mauler, Maximilian; Seyfert, Julia; Haenel, David; Seeba, Hannah; Guenther, Janine; Stallmann, Daniela; Schoenichen, Claudia; Hilgendorf, Ingo; Bode, Christoph; Ahrens, Ingo; Duerschmied, Daniel
Abstract : Technique to measure murine and human PNC formation in whole blood samples. Abstract : Platelets form complexes with neutrophils during inflammatory processes. These aggregates migrate into affected tissues and also circulate within the organism. Several studies have evaluated platelet‐neutrophil complexes as a marker of cardiovascular diseases in human and mouse. Although multiple publications have reported platelet‐neutrophil complex counts, we noticed that different methods were used to analyze platelet‐neutrophil complex formation, resulting in significant differences, even in baseline values. We established a protocol for platelet‐neutrophil complex measurement with flow cytometry in murine and human whole blood samples. In vitro platelet‐neutrophil complex formation was stimulated with ADP or PMA. We tested the effect of different sample preparation steps and cytometer settings on platelet‐neutrophil complex detection and noticed false‐positive counts with increasing acquisition speed. Platelet‐neutrophil complex formation depends on platelet P‐selectin expression, and antibody blocking of P‐selectin consequently prevented ADP‐induced platelet‐neutrophil complex formation. These findings may help generating more comparable data among different research groups that examine platelet‐neutrophil complexes as a marker for cardiovascular disease and novel therapeutic interventions.